2005
DOI: 10.1038/sj.cdd.4401584
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of apoptosis induction by the HIV-1 envelope

Abstract: The envelope glycoprotein complex (Env) of human immunodeficiency virus-1 (HIV-1) can induce apoptosis by a cornucopia of distinct mechanisms. A soluble Env derivative, gp120, can kill cells through signals that are transmitted by chemokine receptors such as CXCR4. Cell surface-bound Env (gp120/gp41), as present on the plasma membrane of HIV-1-infected cells, can kill uninfected bystander cells expressing CD4 and CXCR4 (or similar chemokine receptors, depending on the Env variant) by at least three different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
138
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 75 publications
3
138
0
1
Order By: Relevance
“…mTOR and CD4 + -T-cell loss mTOR activation seems to play a pathogenetic part in the dysregulated apoptosis of CD4 + T cells in HIV-1 patients through gp120-mediated activation of the CD4/CXCR4 (or CCR5)/mTOR/p53 axis [24]. In fact, mTOR can phosphorylate p53 on serine 15 involved in Env-induced syncytial apoptosis [25].…”
Section: Hiv and Its Treatment: Advantages And Some Limits Of Haartmentioning
confidence: 99%
“…mTOR and CD4 + -T-cell loss mTOR activation seems to play a pathogenetic part in the dysregulated apoptosis of CD4 + T cells in HIV-1 patients through gp120-mediated activation of the CD4/CXCR4 (or CCR5)/mTOR/p53 axis [24]. In fact, mTOR can phosphorylate p53 on serine 15 involved in Env-induced syncytial apoptosis [25].…”
Section: Hiv and Its Treatment: Advantages And Some Limits Of Haartmentioning
confidence: 99%
“…While HIV envelope glycoprotein has been implicated in the loss of bystander cells by apoptosis, the mechanism by which envelope mediates this process remains highly debated [51]. Early studies indicated that binding of cell surface associated gp120 subunit of envelope on infected cells with uninfected cells leads to apoptosis [52].…”
Section: Mechanisms Of Hiv-1 Gp41 Induced Pathogenesismentioning
confidence: 99%
“…In vivo circulating immune complexes and replicationincompetent viruses that contain gp120 could induce cell death in a similar manner. 11 Moreover, during HIV-1 infection, there is an increase of circulating anti-CD4 antibodies and more importantly of soluble gp120, anti-gp120 antibodies, and a large number of defective virions, all of which can lead to a www.nature.com/cdd chronic and significant degree of CD4-mediated activation and cell death in uninfected CD4 þ cells 12,13 Highly active ARV therapy (HAART), combining HIV reverse transcriptase and protease inhibitors, leads to a decrease in plasmatic and lymphoid tissue viral load, that may reach undetectable levels, and a concomitant increase in CD4 T-cell numbers. Several mechanisms are involved in the quantitative restoration of CD4 þ T cells, including homeostatic peripheral proliferation, central (thymic) production of new T cells and increased lymphocyte survival (reviewed by Gougeon 1 ).…”
mentioning
confidence: 99%